2006
DOI: 10.1152/ajpheart.01107.2005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hypoxia, anoxia, and metabolic inhibitors on KATP channels in rat femoral artery myocytes

Abstract: Effects of hypoxia, anoxia, and metabolic inhibitors on KATP channels in rat femoral artery myocytes. Am J Physiol Heart Circ Physiol 291: H71-H80, 2006. First published February 17, 2006 doi:10.1152/ajpheart.01107.2005.-Vascular ATP-sensitive potassium (KATP) channels have an important role in hypoxic vasodilation. Because KATP channel activity depends on intracellular nucleotide concentration, one hypothesis is that hypoxia activates channels by reducing cellular ATP production. However, this has not been r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0
1

Year Published

2007
2007
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 48 publications
2
23
0
1
Order By: Relevance
“…In some studies, hypoxia activated glibenclamide-sensitive K ϩ currents in amphotericin B-perforated cells of isolated porcine coronary SMCs (44) and hypoxia-induced relaxation was at least partially inhibited by K ATP blockers in thoracic aorta (91) and cremaster (108), carotid (215), and cerebral (64) arteries. However, in other studies, hypoxia did not increase K ATP current of voltage-clamped, amphotericin B-perforated cells (108,182) and hypoxic relaxations were resistant to glibenclamide (204). Whether these variations in findings are due to species and/or vascular bed differences is unclear.…”
Section: Circulatory Systemmentioning
confidence: 84%
“…In some studies, hypoxia activated glibenclamide-sensitive K ϩ currents in amphotericin B-perforated cells of isolated porcine coronary SMCs (44) and hypoxia-induced relaxation was at least partially inhibited by K ATP blockers in thoracic aorta (91) and cremaster (108), carotid (215), and cerebral (64) arteries. However, in other studies, hypoxia did not increase K ATP current of voltage-clamped, amphotericin B-perforated cells (108,182) and hypoxic relaxations were resistant to glibenclamide (204). Whether these variations in findings are due to species and/or vascular bed differences is unclear.…”
Section: Circulatory Systemmentioning
confidence: 84%
“…(a) Control solutions (either for imaging or electrophysiology) were mixed with freshly prepared sodium dithionite (Na 2 S 2 O 4 ) solution to give a final 1 mM concentration sufficient to reduce pO 2 to low levels (21,22); pH was adjusted to 7.4, and the solution was bubbled with 100% N 2 . (b) Normal media were bubbled for Ͼ30 min with 100% N 2 .…”
Section: Methodsmentioning
confidence: 99%
“…The mediator, in turn, alters the function of one or more effectors, which ultimately mediate the physiological response of the system (3, 58). Numerous experimental evidences point to the mitochondrial electron transport chain (mETC) as the sensor, reactive O 2 species (ROS) as mediators, and K ϩ channels as effectors of the vascular response to acute hypoxia (3,10,26,35,44,52,53,55,56,58,59), and it has been suggested that differences between pulmonary and systemic arteries in this sensing/signaling system may account for the opposite responses of these vessels to the hypoxic stimulus (52).The present information about the response to hypoxia in blood vessels from nonmammalian species suggests largely similar mechanisms as in mammals (32,42,43). In the last few years, the chicken embryo/fetus has emerged as a suitable model for the study of numerous aspects of developmental vascular biology, including the response to acute and chronic changes in oxygenation (1,9,38,39,47,50,51,63).…”
mentioning
confidence: 99%